Epidemiologic profile of epilepsy deaths in the State of Tocantins between 2009 and 2019 (Research, Society and Development, 2022)
Epilepsy is a common chronic neuropathology that afflicts around 1% of the world's population and affects all ages from infants to adults. Due to the characteristics of epileptic crises, there is a two to three times greater risk of mortality from different causes, the most common being neurocysticercosis, accidents, trauma, and sudden death. Therefore, the purpose of this study was to identify the epidemiological profile of deaths from epilepsy in the state of Tocantins which occurred between 2009 and 2019. The study is descriptive research and includes the deaths recorded in the Mortality Information System in the State of Tocantins, where the basic cause was epilepsy. There have been 256 identified deaths with the underlying cause being epilepsy (ICD-10 G40) in the period from 2009 to 2019, with 68% being males. A total of 58% of the deaths were among individuals aged between 20 and 49 years old. The mortality rate due to epilepsy in Tocantins in 2019 was 1.97 (per 100,000 inhabitants), exceeding the rate of the Northern region (1.10) and of Brazil (1.56). Epilepsy mortality represents a public health issue in Tocantins. When timely diagnosed and identified, epileptic seizures can be prevented, whereas antiepileptic drugs are effective and safe in most cases. The failures in the implementing of preventive measurements need to be overcome, being essential the search for strategies to identify risk factors and causes of epileptic crises to allow planning of prevention and control programs.